HUBUNGAN ANTARA INTERAKSI SOSIAL TEMAN SEBAYA DENGAN KEMANDIRIAN PERILAKU REMAJA ( Studi Korelasional terhadap SMP N 1 Padang Panjang ) - Hasti, Ridia; Nurfarhanah, Nurfarhanah (Universitas Negeri Padang, 2013)
The ability of young people in foster independence behavior may be influenced by the social interaction of its peers. Phenomenon in the field most of the students like friends mocked when conveying ideas, some students lacked the courage to speak in front of friends and most difficult students convey their ideas to friends. The research aims to reveal how the relationship between social interaction with peers independence teenage behavior. Quantitative research methods to the type of correlational research. Student population SMP Negeri 1 Padang Panjang 703 people. Proportional sampling technique is random sampling with sample 88 people. The data analysis technique Pearson Product Moment formula with the program Statistical Product and Service Solution for windows release 17.0. There is a significant relationship between social interaction with peers independence adolescent behavior Pearson correlation of 0.389 significance level of 0.000, the relationship enough. Recommended for guidance counselor in order to improve counseling services and a facilitator to develop peer social interaction and independence behavior.